The Problem of Ubication of the Vellanis, Vindenae Road Stop and Ad Fines on the Lisus–Naisus Road (Upper Moesia) - Samardžić, Gligor (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
The paper presents data on the problem of ubication of the Vellanis, Vindenae road stop and Ad Fines on the Lisus–Naisus Roman road (Upper Moesia). The Lisus–Naisus road intersected modern-day Kosovo and Metohija from southwest to northeast. Being the main road, it connected coastal areas to the inland. A modest number of milestones was found at certain points along the road. They are of highly significant historic value due to the fact that they respresent firsthand evidence on the existence of the Roman road in Kosovo and Metohija. There are various opinions about the ubication of the aforementioned road stops in modern historiography. Ptolemaeus mentiones a settlement Vellanis after the Vicianum road stop on the Lisus–Naisus road, but he does not categorize it as the road stop. According to some researchers, Vellanis is identical to the Vicianum stop in Tabula Peutingeriana. We believe that the name of Vellanis mentioned by Ptolemaeus and Ravenna geographer conceals the name of the Vicianum road stop from Tabula Peutingeriana. In regards to the ubication of the Vindenae road stop in the modern scientific research, the prevailing opinion is based on Tabula Peutingeriana as well as the remains of the Roman settlement and necropolis (a monumental building, ceramic dishes, glass, nails, jewellery, money). It is believed that the Vindenae road stop should be looked for near Podujevo, in the area of Glavnik village (Poljanice). Taking Tabula Peutingeriana into consideration as well as the results of modern studies, the Ad Fines road stop should be looked for at the mouth of the Kosanica into the Banjska River, near modern-day Kuršumlija. Various opinions will most certainly exist as long as the assumptions continue to be based on analyses of written historical sources, without systematic archeological excavations and research. What we can say with certainity is that life evolved continously in this area (Upper Moesia), starting from the ancient times till modern days and archeological findings from these sites prove that.
Keywords: Vellanis; Vindenae; Ad Fines; Lisus; Naisus; the Roman road; a road stop; Dardania; Upper Moesia